Body Mass Index and Ventilator Dependence in Critically Ill Subjects in Japan: A Cohort Study Using a Nationwide Database. - Jun Fujinaga; Etsuji Suzuki; Hiromasa Irie; Mutsuo Onodera (Respiratory Care, 2021)
BACKGROUND: Body mass index (BMI) can be an important indicator for health outcomes among critically ill patients. However, the association between BMI and ventilator dependence at ICU discharge among these patients remains unknown. We aimed to evaluate the association between BMI at ICU admission and ventilator dependence at the time of ICU discharge. As secondary outcomes, we used ICU mortality, hospital mortality, and implementation of tracheostomy during ICU stay. METHODS: This is a retrospective cohort study. The data were derived from The Japanese Intensive Care Patient Database, a nationwide ICU database in Japan. We included all patients in the registry who were ≥ 16 y old, received mechanical ventilation, and were admitted to an ICU between April 2018 and March 2019. On the basis of their BMI at ICU admission, subjects were classified as underweight (< 18.5 kg/m²); normal weight (≥ 18.5 kg/m² to < 23 kg/m²); overweight (≥ 23 kg/m2 to < 27.5 kg/m²); or obese (≥ 27.5 kg/m²). RESULTS: Among 11,801 analyzed subjects, 388 (3.3%) subjects were ventilator-dependent at ICU discharge. Compared with normal-weight subjects, the risk for ventilator dependence at ICU discharge increased among underweight subjects even after adjusting for potential confounders and inter-ICU variance in 2-level multivariable logistic regression analysis (odds ratio 1.46 [95% CI 1.18-1.79]). Although obesity was also associated with a higher risk of ventilator dependence, the association was less clear (odds ratio 1.10 [95% CI 0.99-1.22]). The risk of ICU mortality, hospital mortality, and implementation of tracheostomy also increased in underweight subjects. CONCLUSIONS: Critically ill underweight subjects had a higher risk of ventilator dependence at ICU discharge compared to normal-weight subjects, even after adjusting for potential confounders and inter-ICU variance. The association between BMI and ventilator dependence should be examined using information on subjects' nutritional status and frailty in further studies.